Ціна як істотна умова договору на виконання науково-дослідних або дослідно-конструкторських та технологічних робіт - Великанова, Марина Миколаївна (My University, 2010)
В статье проанализированы способы определения цены за договором на выполнение научно-исследовательских или опытно-конструкторских и технологических работ и приведены рекомендации по формировании цены при выполнении таких работ.

In the article methods of determination of price are analysed by agreement on implementation of research or doslidno-konstruktorskikh and technological works and resulted recommendations in relation to forming of price at implementation of such works.
Keywords: засоби визначення ціни; умови договору; науково-дослідні роботи; дослідно-конструкторські роботи; технологічні роботи; формування ціни; способы определения цены; условия договора; научно-исследовательские работы; опытно-конструкторские работы; технологические работы; формирование цены; methods for determining the price; terms of an agreement; research and development; development activities; engineering works; pricing